Association between morphometric variables and nocturnal desaturation in sickle-cell anemia - Cristina Salles; Marcelo Bispo; Regina Terse Trindade-Ramos (Elsevier, 2014)
OBJECTIVE: to evaluate associations between morphometric variables, cervical circumference (CC), and abdominal circumference (AC) with the presence of nocturnal desaturation in children and adolescents with sickle-cell anemia. METHODS: all patients were submitted to baseline polysomnography, oral cavity measurements (maxillary intermolar distance, mandibular intermolar distance, and overjet), and CC and AC measurements. RESULTS: a total of 85 patients were evaluated. A positive correlation was observed between the height/age Z-score and CC measurement (r = 0.233, p = 0.031). The presence of nocturnal desaturation was associated with CC (59.2± 9.3 vs. 67.5 ± 10.7, p = 0.006) and AC measurements (27.0 ± 2.0 vs. 29.0± 2.1, p = 0.028). There was a negative correlation between desaturation and maxillary intermolar distance (r = -0.365, p = 0.001) and mandibular intermolar distance (r = -0.233, p = 0.037). CONCLUSIONS: the morphometric variables of CC and AC may contribute to raise suspicion of nocturnal desaturation in children and adolescents with sickle-cell anemia.